Fabrikasi Bearing Tracker Ukuran Jangkauan Diameter 90mm, Diameter Bearing 75mm, Kapasitas 2 Unit/Jam - Deivan Pratama; Syamsul Hadi; Ahmad Irsyad Nur Habibi; Gusti Ramdhani Hermasyah Putra; Hazel Xavier Zhendi; Muhammad Alea Putra Nurshoba (Jurnal Kendali Teknik dan Sains, 2026)
The difficulty of installing or removing the inner ring of the rolling bearing on its axis and installing or removing the outer ring of the rolling bearing on its housing are the problems faced. The purpose of fabrication is to obtain a tool for installing or removing the ring from the rolling bearing (bearing tracker) with a diameter range of 90 mm for a rolling bearing diameter of 75 mm whose dimensions match the dimensions of the rolling bearing. The fabrication method includes: design of auxiliary equipment for installing and removing rolling bearings, raw material selection, raw material cutting, component turning, component drilling, component welding, finishing-assembly, and quality and dimension inspection. The fabrication results are bearing trackers with a diameter range of 90 mm for a rolling bearing diameter of 75 mm whose dimensions match the dimensions of the rolling bearing, the total production cost is Rp. 240,000,-/unit, and the process duration is 30 minutes/unit which implies that the bearing tracker is able to work effectively as an auxiliary tool for installing or removing the inner or outer ring of the rolling bearing, safer steps, and more practical than manual methods.